MANAJEMEN PEMBIAYAAN PENDIDIKAN DALAM TRISENTRA BIAYA: INVESTASI, OPERASIONAL, DAN PERSONAL UNTUK PENINGKATAN MUTU DI SMAN 1 KEDUNGWARU - Desy Islamiati; Saraswati Saraswati; Erwin Arianto (STKIP Pesisir Selatan, 2026)
This study aims to describe financing management in improving educational quality at SMAN 1 Kedungwaru Tulungagung, with sub-focuses on: (1) investment costs, (2) operational costs, and (3) personal costs. A qualitative approach with a single case study design was employed. Data collection techniques included in-depth interviews, participatory observation, and school archive documentation. Data validity was ensured through extended observation, increased researcher persistence, and triangulation. Data analysis employed an interactive model encompassing reduction, presentation, and conclusion drawing, producing valid and accountable findings. Investment costs were focused on building renovation, human resource development (subject teacher working groups/MGMP, workshops, classroom action research/PTK, ICT training), and working capital sourced from BPOPP, BOS, and community participation, all integrated within the School Budget Activity Plan (RKAS). Operational costs covered educator salaries, consumable materials, extracurricular activities, and services, with monthly online reporting monitored by the Provincial Budget Authorization Officer (KPA). Personal costs are only collected during the new student admission period (PPDB), with 15% of economically disadvantaged students receiving fee reductions. Financing management at SMAN 1 Kedungwaru is carried out in a systematic, transparent, and accountable manner through real-time digital oversight by the Provincial KPA, demonstrating that the quality of governance not merely the size of the budget is the primary determinant of educational quality improvement.